ADHD symptoms and smoking outcomes in a randomized controlled trial of varenicline for adolescent and young adult tobacco cessation. (1st March 2023) - Green, ReJoyce; Baker, Nathaniel L.; Ferguson, Pamela L.; Hashemi, Daniel; Gray, Kevin M.
Abstract: Background: Most adult daily smokers try their first cigarette during adolescence. Attention-Deficit Hyperactivity Disorder (ADHD) in adolescents is associated with increased risk for cigarette smoking. The impact of ADHD symptoms on smoking cessation among adolescents has been less well-studied. The present secondary data analysis from a clinical trial of varenicline examined ADHD symptoms as a moderator of smoking cessation in adolescents and young adults. Methods: The double-blind, placebo-controlled trial included treatment-seeking daily cigarette smokers ages 14 – 21 ( N = 157) randomized to receive a 12-week course of varenicline or placebo, added to weekly smoking cessation counseling. At pre-treatment assessment, participants were administered a self-report measure of ADHD symptoms, the ADHD – Rating Scale (ADHD-RS). High (≥5) versus low (<5) and continuous ADHD-RS symptom counts in both hyperactive/impulsive (HI) and inattention (IA) domains were examined as predictors of smoking outcomes. Results: Participants with high IA symptoms at baseline were less likely to achieve 7-day point prevalence abstinence (PPA) at weekly visits ( p = .001) during active treatment and end-of-treatment ( p = .002) compared to those with low IA symptoms. In contrast, high HI symptoms did not predict differences in 7-day PPA or end-of-treatment abstinence versus low symptoms ( p's ≥ .07). These findings were not modified by varenicline versus placebo treatment assignment. Conclusions: ADHD IA symptoms were associated with poorer cessation outcomes among adolescent smokers. These findings warrant additional investigation into how ADHD symptoms may be accounted for in smoking cessation interventions for adolescents and young adults. Highlights: Few studies have examined the impact of ADHD symptoms count on smoking outcomes. Greater inattentive symptoms predicted less abstinence and more cigarettes per day. Hyperactive-impulsive symptoms did not consistently predict smoking outcomes. Varenicline did not moderate the effect of ADHD symptoms on smoking cessation.